UTILITY OF APACHEII, SAPS II, AND SOFA SCORES AS INDICATORS OF SEVERITY OF SEPSIS AND PREDICTORS OF MORTALITY IN A TERTIARY CARE HOSPITAL - MITTAL, MOHIT; HIREMATH, RAVISHEKAR N; GAUR, NIMISH; GHODKE, SANDHYA; BASRA, SHARANJIT SINGH; VERMA, VISHAL; SREENIVAS, AUDUKOORI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to predict the outcome and mortality of patients with sepsis in a tertiary care hospital using defined scores such as APACHE II, SAPS II, and SOFA scores. Methods: This prospective and observational study was carried out in intensive care units (ICUs) setup of multispecialty hospital in Western Maharashtra. Sample size was 90 patients with sepsis who were admitted to ICU (surgical) directly or indirectly, during the duration of 1 1/2 month. The study was approved by the Institutional Ethical Committee and written informed consent from all the patients or their guardians/legal representatives. The detailed history, clinical examination, and all the relevant laboratory investigations were done including blood culture. The parameters as mentioned in APACHEII, SAPS II, and SOFA scores were recorded daily. For statistical analysis, Chi-square test, Fisher’s exact test, MannWhitney test, and Binary Logistic Regression were used. SPSS software was used for analysis. Results: Out of these 90 patients, 64 (71.1%) were males and 26 (28.8%) were females. Mean age of the study population was 61.86 years. Mean duration of stay in the ICU was found out to be 3.33 days. Culture positivity was found in 53 cases (58.8%). Gram-negative organisms were responsible for 37 (69.8%) cases while Gram-positive organisms were responsible for 16 (30.1%) cases. Statistics of various variables among cases and other detailed results were studied. SOFA score (p=0.046) and APACHE II score (p=0.00042) have been found to be statistically significant predictors of “Death”; higher the SOFA score and APACHE II score-more probability of patient dying. However, mortality as per SAPS II (p=0.202) was not found to be statistically significant predictor of death. Conclusions: APACHE II, SAPS II, and SOFA scores can be used for prediction of mortality by using appropriate statistical tests. People of older age, male gender, and preexisting chronic health conditions are chiefly prone to develop Septic shock; hence, prevention strategies should be targeted at these susceptible populations. The epidemiology of Septic shock in developing countries warrants greater attention in the future studies.